Upaya Pembentukan Sikap Sosial Melalui Pendidikan Karakter Siswa Kelas VIII Di SMP Negeri 1 Kalidawir - Deandra Myana Rahayu Ningrum; Jani Jani (JISPENDIORA Jurnal Ilmu Sosial Pendidikan Dan Humaniora, 2024)
Today’s young generation is starting to lose their social attitudes. Likewise, what happened at SMP Negeri 1 Kalidawir, where the majority of students had poor attitudes, such as lack of politeness, lack of discipline, lack of concern for others, and lack of responbility. The focus of this research is (1) Implementation of character education at SMP Negeri 1 Kalidawir Tulungagung, (2) How social attitudes are formed through character education for class VIII students at SMP Negeri 1 Kalidawir Tulungagung, (3) What are the obstacles that occur during the process of forming social attitudes through character education for class VIII studens at SMP Negeri 1 Kalidawir Tulungagung, (4) What is the impact of character education on the social attitudes of class VIII students at SMP Negeri 1 Kalidawir Tulungagung. This study used descriptive qualitative method. The results obtained from this research are (1) Implementation of character education is carried out during guidance counseling for students and during the learning process in class. (2) Efforts to form social attitudes are made by accuctoming students to be honest, disiplined, responsible, polite and caring. (3) Obstacles that occur during the process of forming social attitudesinclude differences in student character, family fakctors, and the influence pf the social environment. (4) the impact of charakter education in the form of positive impacts which include decreasing student violation points, improving student behavior and improving student social attitudes; as well as negative impacts in the form of students who are still not doing well